Anukta Dravya Adhyayan – Stevia Rebaudiana - Upadhyay, Bhavana Madhusudan; Kaushal, Kamini; Sharma, Aarti (International Research Journal of Ayurveda & Yoga, 2021)
The emergence of chemical molecules has been a blessing for combating several diseases, but it has paved the way for troublesome situations such as various adverse effects, the emergence of resistance and so on. Various research has been underway on new molecules to find out the least effects and having a better potency is currently on its way and more concentration is being given upon traditional plants in order to avoid these aforementioned problems. Medicinal plants have been recognized to have potential drug uses. Any dysregulation is avoided due to the sweetness imparted by its glycosides and is known by it. The evaluation by phytochemical studies concluded the existence of tannins, alkaloids, glycosides, saponins, sterols, triterpenes with various potentials.[5][6] The purpose of this review is to understand the medicinal potential of stevia and its acceptance as a significant raw material for human diet.